THE EFFECT OF GREEN ACCOUNTING AND MATERIAL FLOW COST ACCOUNTING ON THE FINANCIAL PERFORMANCE OF PLASTIC AND PACKAGING SECTOR COMPANIES IN THE 2022-2024 PERIOD - Depi, Candra; Sri Utami, Endang (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of Green Accounting and Material Flow Cost Accounting (MFCA) on the financial performance of companies in the plastic and packaging sector listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. The research method employed is quantitative with a descriptive approach and multiple linear regression analysis using SPSS 21 software. The data used is secondary data from plastic manufacturing companies registered on the Indonesia Stock Exchange.The results indicate that Green Accounting has a significant effect on the company's financial performance. In contrast, Material Flow Cost Accounting has no substantial impact on the company's financial performance. This research makes essential contributions by focusing on the plastic sector, which faces significant environmental challenges. It identifies opportunities for further research on the effectiveness of sustainable accounting practices in enhancing financial performance. The study also emphasizes the importance of optimizing material usage and environmental awareness in sustainable business practices.